Specters of the Atlantic : Finance Capital, Slavery, and the Philosophy of History - Baucom, Ian, 1967- (Book collections on Project MUSE., 2005)
Cultural and literary study of the 1781 massacre on the slaveship Zong for the insurance money and the aftereffects of the event on the development of modernity.